EMPAT METODE DALAM PENAFSIRAN AL-QUR’AN - Abdul Manaf (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2023)
Early interpretations of Islam were carried out by taking several steps of interpretation. However, at this time the term method of interpretation was not yet known as the tendency of the mufasir. The term of tafsir method was known in the modern age. The method directs someone to determine the best steps in understanding the verses of the Qur’an according to the scientific background and the purpose of the mufasir. In addition, determining the tafsir method can adjust between the needs of interpretation and the conditions of society. Thus, it is truly true that the saying that Al-Qur’an is always in accordance with the times. This study aims to find out the variety of interpretation methods that are currently developing, the steps of interpretation of each method, the advantages and disadvantages contained in each method, and what tafsir books have applied the interpretation method in their tafsir books. There are four methods that are widely known among people who are engaged in the science of Al-Qur’an and Tafsir, namely the tahlili method, the ijmali method, the muqaran method, and the maudu'i method. These four methods are known by several terms, namely manhaj, tariqah, and uslub.